DOZ047.119: Five year experience of a tertiary-level referral center in children with anastomotic strictures after esophageal atresia repair. (24th June 2019) - Contini, A C I; Rea, F; Guerra, L; Caldaro, T; Torroni, F; Tambucci, R; Angelino, G; De Angelis, P; Balassone, V; Romeo, E; Faraci, S; Federici di Abriola, G; et al.
Abstract: Background: Esophageal atresia (EA) is the most common congenital anomaly of the esophagus. Anastomotic strictures (AS) frequently occur in patients surgically treated for esophageal atresia (EA). The primary aim of this study is to determine the role of esophageal dilations in the management of AS in childhood after reconstruction of EA. Methods: A retrospective chart review of patients treated with esophageal dilation for EA was conducted at our tertiary referral center from 2013 to 2017. We included patients treated at our Institution since diagnosis and patients referred from other Institutions. All dilations were performed with Savary-Gilliard polyvinyl bougies. Dilation was performed on an 'as needed' basis. Results: Eighty-nine patients (68.5% males, 31.5% female) underwent 433 dilations overall in the study period (median: 3, range: 1–36). Type I of EA was 26.1%, Type II was 9.1%, Type III was 64.8%. Associated malformations in 52.8% cases. Six patients received 33 local applications of mitomycin C (MMC) and two of triamcinolone acetate for recurrent stenosis. Four patients developed a preanastomotic diverticulum-treated endoscopically. Nine patients (10.1%) underwent dynamic esophageal stent placement after a median of six dilations. Antireflux surgery was performed in 28 patients (31.5%), Nissen fundoplication in 20 patients, Toupet in 6, and both in 2. Patients treated with antireflux surgery received a mean of 7.1 dilations before surgery, versus 3.9 in patients without antireflux surgery ( P  = 0.0285, unpaired t test). Seven patients (7.9%), 5 referral, needed major esophageal surgery (4 esophageal reanastomosis and 3 esophagocolonplasty). Patients underwent major surgery received a mean of 19.3 dilations versus 3.6 dilations in no-surgery patients ( P  = 0.0002, Mann-Whitney U test). Six of 9 stented patients did not require surgery. Perforation was present in 0.4% of 433 dilatations. Conclusions: Esophageal dilatation remains the mainstay of treatment for AS after EA repair. Stricture resection with end-to-end anastomosis is the reconstructive option of choice; esophageal substitution is reserved only in cases of intractable stricture. The use of esophageal dynamic stent, MMC, or steroids could help in avoiding or delaying the need of operative stricture resection. Antireflux surgery is mandatory in case of severe pathological gastroesophageal reflux to prevent intractable strictures from developing.